Loss of carbohydrate during training, processing, pipeline transportation oil and oil products - Кальницька, Ю.А.; Бойченко, С.В. (Proceedings of National Aviation University (archive), 2006)
The line of prevention of hydrocarbon raw material losses as effect of the evaporation is to bepropound in accordance with the established order of common falling-off and condition of Fuel-Energy Complex.